Comparing silicone-coated self-adhesive absorbent polyurethane films with transparent absorbent films for bilateral hip dressing: a prospective randomized controlled trial - Chirathit Anusitviwat; Varah Yuenyongviwat (Journal of Orthopaedic Surgery and Research)
Abstract Background Silicone-coated self-adhesive absorbent (SSA) and transparent films with absorbent (TFA) dressings are reportedly effective postoperative knee surgery dressings; however, there have been no direct comparative studies on these two innovative dressings over the hip areas. In this study, we aimed to compare user satisfaction and potential complications between TFA and SSA dressings for the hip area. Methods This prospective randomized controlled trial was conducted at a tertiary hospital. The hip side to receive the polyurethane film with SSA dressing (Mepilex® Border Post-Op) was randomly allocated. The other side of the hip was covered with TFA (OPSITE Post-Op). Participants were scheduled for follow-ups 7 and 14 days after the initial application. Between-group outcomes were compared using a two-sample t-test or Wilcoxon signed-rank test for continuous variables and McNemar’s chi-square test for categorical variables. Results Thirty-two participants (30 − 60 years) without a history of hip surgery were included in the study. The participants were predominantly female, with a mean age of 42.8 years. Pain, difficulties in daily activities, and satisfaction scores were similar between the groups. However, moisture accumulation was significantly higher with the TFA dressing (37.9% vs. 13.8%, p < 0.01), with more dressing failures (34.5% vs. 20.7%, p = 0.016) and complications (37.9% vs. 17.2%, p = 0.012) at the 14-day follow-up than with the SSA dressing. Conclusions SSA dressings are preferable for hip wound care because of better moisture management, fewer dressing changes required, and fewer complications if applied for > 7 days. Both dressings offered high user satisfaction, minimal pain, and minor difficulties in daily activities.